Diversity in trap color and height increases species richness of bark and woodboring beetles detected in multiple funnel traps - Jon Sweeney; Wentao Gao; Jerzy M. Gutowski; Cory Hughes; Troy Kimoto; Chantelle Kostanowicz; Yan Li; Chris J. K. MacQuarrie; Peter Mayo; Qingfan Meng; Tomasz Mokrzycki; Peter Silk; et al. (PLoS ONE, 2025)
Early detection of non-native, potentially invasive bark beetles and woodboring beetles (BBWB) (Coleoptera: Buprestidae, Cerambycidae, Disteniidae; Curculionidae: Scolytinae) inadvertently introduced to new habitats via global trade is a critical issue for regulatory agencies in numerous countries. We conducted trapping experiments to evaluate the effects of trap color (black vs. green vs. purple) and trap height (canopy vs. understory) on detection of BBWB in Canada, Poland, USA, and China, using Fluon-treated 12-unit multiple-funnel traps. Each trap was baited with the same pheromone and ethanol lures known to attract several species of BBWB. We predicted BBWB species composition would differ between vertical strata and among trap colors, and that the number of BBWB species detected would increase with greater diversity of trapping methods, i.e., by using more than one color of trap and by placing traps in both the canopy and understory. Our prediction was partially supported, i.e., placing one color of trap in the understory and a different colored trap in the canopy detected more species than did a single trap color placed in either the understory or canopy. However, the combinations of trap height and colors that detected the most species varied among sites. The community of BBWB species captured in traps was significantly affected by trap height and trap color at all sites, with the strongest patterns in the data from Poland and the USA. Black and purple traps caught similar communities of BBWB species in the canopy and understory, but green traps caught a different species assemblage in the canopy in Poland and the USA. Effects of trap height and color on species richness were consistent across all four sites within the subfamilies Agrilinae (more species captured in green canopy traps than any other trap height-color combination), Chrysochroinae (more species captured in purple canopy traps than any trap height-color combination) and Scolytinae (more species captured in the understory than the canopy and no effect of trap color), but varied significantly among sites within Cerambycidae subfamilies. None of the species accumulation curves reached an asymptote for any trap color-height combination at any site, indicating that 8–9 traps per site were not sufficient to detect all BBWB species present. Thus, increasing the number of traps deployed per site will increase the BBWB species richness captured and the chances of detecting non-native species that may be present.